Enhanced biomethane potential from wheat straw by low temperature alkaline calcium hydroxide pre-treatment. (August 2015) - Reilly, Matthew; Dinsdale, Richard; Guwy, Alan
Highlights: Ambient temperature Ca(OH)2 treatment improves the methane yield from wheat straw. Interactions exist between alkali treatment, cellulase addition and particle size. Most effective treatment blend was size reduction to 3 mm with Ca(OH)2 treatment. Ca(OH)2 treatment of 3 mm straw saw a 15 day yield of 290 NmL-CH4 g-VS −1 . Little effect of alkaline pre-treatment on lignin composition was seen. Abstract: A factorially designed experiment to examine the effectiveness of Ca(OH)2 pre-treatment, enzyme addition and particle size, on the mesophilic (35 °C) anaerobic digestion of wheat straw was conducted. Experiments used a 48 h pre-treatment with Ca(OH)2 7.4% (w/w), addition of Accellerase®-1500, with four particle sizes of wheat straw (1.25, 2, 3 and 10 mm) and three digestion time periods (5, 15 and 30 days). By combining particle size reduction and Ca(OH)2 pre-treatment, the average methane potential was increased by 315% (from 48 NmL-CH4 g-VS −1 to 202 NmL-CH4 g-VS −1 ) after 5 days of anaerobic digestion compared to the control. Enzyme addition or Ca(OH)2 pre-treatment with 3, 2 and 1.25 mm particle sizes had 30-day batch yields of between 301 and 335 NmL-CH4 g-VS −1 . Alkali pre-treatment of 3 mm straw was shown to have the most potential as a cost effective pre-treatment and achieved 290 NmL-CH4 g-VS −1, after only 15 days of digestion.